Precalculus : algebraic and trigonometric functions, vol. 5 : Matrices, determinants, and mathematical induction (San Rafael, California : Individual Learning Systems, Inc., 1971)
In unit six you will learn a method of proof called mathematical induction that allows you to prove special types of statements. You will apply this method of proof to prove the binomial theorem, an important theorem used to expand a binomial raised to a power.
Unit Six: Matrices, determinants, and mathematical induction -- Module 21. matrices -- Module 22. Introduction to determinants -- Module 23. Solving systems of linear equations with determinants -- Module 24. Mathematical Induction -- Module 25. The binomial theorem.
Keywords: PRECALCULUS -- MATRICES -- DETERMINANTS -- MATHEMATICAL INDUCTION